The expression landscape of cachexia‐inducing factors in human cancers. Issue 4 (3rd March 2020) - Freire, Paula Paccielli; Fernandez, Geysson Javier; de Moraes, Diogo; Cury, Sarah Santiloni; Dal Pai‐Silva, Maeli; dos Reis, Patrícia Pintor; Rogatto, Silvia Regina; Carvalho, Robson Francisco
Abstract: Background: Cachexia is a multifactorial syndrome highly associated with specific tumour types, but the causes of variation in cachexia prevalence and severity are unknown. While circulating plasma mediators (soluble cachectic factors) derived from tumours have been implicated with the pathogenesis of the syndrome, these associations were generally based on plasma concentration rather than tissue‐specific gene expression levels. Here, we hypothesized that tumour gene expression profiling of cachexia‐inducing factors (CIFs) in human cancers with different prevalence of cachexia could reveal potential cancer‐specific cachexia mediators and biomarkers of clinical outcome. Methods: First, we combined uniformly processed RNA sequencing data from The Cancer Genome Atlas and Genotype‐Tissue Expression databases to characterize the expression profile of secretome genes in 12 cancer types (4651 samples) compared with their matched normal tissues (2737 samples). We systematically investigated the transcriptomic data to assess the tumour expression profile of 25 known CIFs and their predictive values for patient survival. We used the Xena Functional Genomics tool to analyse the gene expression of CIFs according to neoplastic cellularity in pancreatic adenocarcinoma, which is known to present the highest prevalence of cachexia. Results: A comprehensive characterization of the expression profiling of secreted genes in different human cancers revealed pathways and mediators with a potential role in cachexia within the tumour microenvironment. Cytokine‐related and chemokine‐related pathways were enriched in tumour types frequently associated with the syndrome. CIFs presented a tumour‐specific expression profile, in which the number of upregulated genes was correlated with the cachexia prevalence ( r 2 : 0.80; P value: 0.002) and weight loss ( r 2 : 0.81; P value: 0.002). The distinct gene expression profile, according to tumour type, was significantly associated with prognosis ( P value ≤ 1.96 E‐06). In pancreatic adenocarcinoma, the upregulated CIF genes were associated with tumours presenting low neoplastic cellularity and high leucocyte fraction and not with tumour grade. Conclusions: Our results present a biological dimension of tumour‐secreted elements that are potentially useful to explain why specific cancer types are more likely to develop cachexia. The tumour‐specific profile of CIFs may help the future development of better targeted therapies to treat cancer types highly associated with the syndrome.